Applications of circulating tumor cells for prostate cancer - Shirley Cheng; Jie-Fu Chen; Yi-Tsung Lu; Leland W.K. Chung; Hsian-Rong Tseng; Edwin M. Posadas (Asian Journal of Urology)
One of the major challenges that clinicians face is in the difficulties of accurately monitoring disease progression. Prostate cancer is among these diseases and greatly affects the health of men globally. Circulating tumor cells (CTCs) are a rare population of cancer cells that have shed from the primary tumor and entered the peripheral circulation. Not until recently, clinical applications of CTCs have been limited to using enumeration as a prognostic tool in Oncology. However, advances in emerging CTC technologies point toward new applications that could revolutionize the field of prostate cancer. It is now possible to study CTCs as components of a liquid biopsy based on morphological phenotypes, biochemical analyses, and genomic profiling. These advances allow us to gain insight into the heterogeneity and dynamics of cancer biology and to further study the mechanisms behind the evolution of therapeutic resistance. These recent developments utilizing CTCs for clinical applications will greatly impact the future of prostate cancer research and pave the way towards personalized care for men. Keywords: Prostate cancer, Circulating tumor cell, Biomarker, Liquid biopsy, Molecular oncology